Ability to Pluralize Nouns - Yunanda, Fachri; Husda, Azizah (English Teaching and Linguistics Journal, 2021)
Every language has its own specific rules in pluralizing nouns. This research found the ability of students in pluralizing nouns in English. Pluralizing nouns is divided into two forms, regular and irregular form. The objectives of the research were to find out their ability and problems to pluralize nouns. The instruments used in this research were test, and interview. The sample of this research was 32 students. Based on the test, the number of the ability was very good, 25% (8 students), good 38% (12 students), and medium, 15% (5 students), while bad 13% (4 students), andvery bad 9% (3 students). The problems were that the students did not know accurately the rules or patterns how to pluralize noun in English especially the irregular ones (63%), not understanding the materials of plural nouns (15%), feeling difficult to apply plural nouns in sentences related to concordances (13%), and Feeling confused with the process of pluralizing irregular nouns dealing with some exceptions (9%).